(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
The cultivation of hybrid tomatoes, intended for fresh consumption, with a determined growth habit, and without support, is an alternative that has a lower production cost. The research aimed to evaluate the productivity and economic viability of different tomato genotypes, with a determinate and indeterminate growth habit. The experimental design was in completely randomized blocks. Ten hybrids and a variety were grown in 2016, and nine hybrids, and a variety in 2018, with a spacing of 0.5 meters between plants. Harvests were carried out in four periods in 2016, at 72, 82, 97, and 105 days after transplanting (DAT); and in 2018 at 81, 87, 97, and 111 DAT. After harvesting, the gross value of production and profit were quantified. The hybrids that obtained the highest production per plant in 2016 were Gabrielle (6,010 kg), with support; Thaise (5.529 kg); and N901 (5.003 kg). In 2018, Dominador and Thaise hybrids had the highest production, with 4.109 and 3.961 kg per plant, respectively. The gross value of tomato production in 2016 was higher than in 2018 for all hybrids and variety, except for Dominador hybrid. Hybrids with a determined growth habit and conducted without support are a profitable alternative to produce tomatoes intended for fresh consumption, especially the hybrid Gabrielle, which had the highest production. The economic viability of hybrids grown without support is superior to all hybrids with support.